“Meaninglessness makes me unhappy”: examining the role of a sense of alienation and life satisfaction in the relationship between the presence of meaning and depression among Chinese high school seniors - Hou, Xiaoxu; Hu, Jinsheng; Liu, Zhihong (Frontiers in Psychiatry, 2025)
IntroductionGiven the high incidence of depression among adolescents and its serious consequences, investigating its influencing factors and mechanisms is of great theoretical and practical significance. This study aims to explore the mediating effects of a sense of alienation and life satisfaction on the relationship between the presence of meaning in life and depression among Chinese high school seniors.MethodsSix hundred and twenty-one senior high school students (17.09 ± 0.45 years, 266 boys) were recruited from Shandong, China, to participate in the study. Participants completed the Adolescent Students’ Sense of Alienation (ASAS), Meaning in Life Questionnaire (MLQ), Satisfaction with Life Scale (SWLS), and Beck Depression Inventory-II (BDI-II).ResultsOur findings revealed that (1) the sense of alienation and life satisfaction play a chain mediating role between the presence of meaning in life and depression among Chinese high school seniors; (2) the sense of alienation plays a mediating role between the presence of meaning in life and depression; (3) there are gender differences in the chain mediation model of the influence of the presence of meaning in life on depression.ConclusionThis study reveals potential pathways through which the presence of meaning in life affects depression among Chinese high school seniors, offering support and a basis for future mental health interventions for this population.